Burdens and psychosocial consequences of the COVID-19 pandemic for Austrian children and adolescents - Eigl, Esther-Sevil; Widauer, Sebastian Stefan; Schabus, Manuel (Frontiers in Psychology, 2022)
OBJECTIVES: The negative psychosocial effects of the COVID-19 pandemic are becoming increasingly apparent. Children and adolescents, in particular, were affected and were torn away from their daily life routines. The aim of our survey is to evaluate the psychosocial burden and impairments of children and adolescents in Austria during the COVID-19 pandemic by use of cross-sectional analysis. SETTING: An Austrian-wide online survey available from February 21st to April 19th, 2021 for children and adolescents. The questionnaire was distributed widely using the national press agency and public media. PARTICIPANTS: Using an online questionnaire, 5483 children and adolescents between 6 and 18 years of age were sampled. OUTCOME MEASURE: Quantitative responses to questions regarding the children’s feelings, worries, and needs regarding the COVID-19 pandemic. Furthermore, the children were sampled for subjective risk perception, as well as their sleep quality. RESULTS: Most children reported a high degree of fear due to the pandemic, with especially female (48.1%) participants being under more emotional strain than their male (35.9%) counterparts. Associated with this, we found a strong overestimation of COVID-19-associated hospitalization likelihood (>100-fold) across all age groups. In addition, an alarming lack of positive perspective during the ongoing pandemic is evident across all age groups including the youngest participants aged 6-10 years. Feelings of anger and annoyance (58.2%), loneliness (46%), and sadness (42.7%) are reported much more frequently than before the pandemic. On the other hand, only 15.6% reported feeling well (or even better; 2%) since the COVID-19 pandemic. Last but not least, our study shows an alarming 37% of children and adolescents now reporting poorer sleep quality than before the pandemic. CONCLUSION: The results of this survey indicate the high burden and emotional strain for children and adolescents during the pandemic. Personal contact with friends and family is mentioned as the most protective factor for their mental health. The study results underscore the need for immediate action to limit the collateral damage that has already occurred on a psychosocial and developmental level among younger generations worldwide.